A Priori and a Posteriori Error Analysis of the Discontinuous Galerkin Methods for Reissner-Mindlin Plates (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, we apply an a posteriori error control theory thatwe develop in a very recent paper to three families of the discontinuous Galerkin methods for theReissner-Mindlin plate problem. We derive robust a posteriori errorestimators for them and prove their reliability and efficiency.